The dystrophinopathies in Costa Rica - Azofeifa, Jorge (2004)
A five-years long study aiming to describe the basic genetic epidemiology of the dystrophinopathies in Costa Rica recruited 31 patients with clinical symptoms of DMD/BMD at the National Children’s Hospital (HNN). This center is the obligate reference hospital of the national health system for genetic diseases, however, the geographic origin of the patients, a low percentage of deletions and a high proportion of de novo mutations found among them indicate that a significant ascertainment bias impedes a substantial scientific approach to confront and alleviate the problems posed by these severe diseases in Costa Rica.